Formal institutional uncertainty and equity sought on foreign market entry: does industry matter?. Issue 3 (15th May 2020) - Ahmed, Kashif; Bebenroth, Ralf; Hennart, Jean-François
Abstract : Purpose: This study aims to examine how the effect of host country formal institutional uncertainty on the percentage of equity sought in cross-border acquisitions (CBAs) is moderated by the host country industry (i.e. targets from the technology versus those from the non-technology industry). Design/methodology/approach: This study is based upon the legitimacy perspective of institutional theory and uses Tobit regression analysis on a sample of 1, 340 CBAs. Findings: Results show that cross-border acquirers prefer a lower equity level for targets in institutionally less developed countries and that this negative effect of the host country institutional risk on the equity percentage sought is more pronounced for technology-based targets. Research limitations/implications: Three major limitations of the study are as follows: The data were collected from only Japanese acquirers. The study measured formal institutional uncertainty by applying only secondary data. The study used the Bloomberg Industry Classification Systems, instead of the Standard Industry Classification that has been used widely in prior studies. Practical implications: This study shows that the industry selected has a bearing on equity sought in CBAs. Investing in institutionally less developed countries is particularly challenging when the targets of acquisition are in the technology industry. Originality/value: To the best of the authors' knowledge, this is the first study that investigates the moderating effects of an industry on the relationship between host country formal institutional uncertainty and the percentage of equity sought in CBAs.